Zubiri, a «Hidden and Shrewd» Hegel Reader. About the Course «Philosophical Reflections on The Aesthetical» - Espinoza Lolas, Ricardo; Lombardo Bertolin, Patricio (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
This article explores the Course of two lessons on the aesthetic, entitled Philosophical reflections on the aesthetic, a «theoretical thread» very little studied by specialists. This course that Zubiri made in 1975, was very old, it is analyzed how the most radical is shown to understand the aesthetic from its philosophical categories, but from the «invisible hand» of Hegel. It is not the Hegel that Zubri explicitly criticizes (and in the text itself) and that always places him in a very distant way to the German thinker, but of the categorial itself of the Hegelian thought that Zubiri «takes a hand» to show how he operates his own of his thought to account for the complex theme of the articulation of the aesthetic and reality. Here we see that Hegel’s thought has much to contribute to understand the aesthetic itself. And this, even, beyond what Hegel himself, as a thinker of his time, philosophized on the subject of art and / or the aesthetic.
Keywords: Zubiri; Hegel; art; reality; matter